Latent profiles of emotion regulation among university students: links to repetitive negative thinking, internet addiction, and subjective wellbeing - Oliveira, Joana; Pedras, Susana; Inman, Richard A.; Ramalho, Sofia Marques (Frontiers in Psychology, 2024)
Recent years have seen a deterioration in the mental health of university students and notable surge in the need for psychological support. Due to its links to psychopathology and high-risk behaviors, difficulty in emotion regulation frequently serves as a transdiagnostic dimension. This cross-sectional study used a person-centered analytical approach (latent profile analysis; LPA) to identify groups of Portuguese university students with similar profiles of emotion regulation difficulties (N = 261; Mage = 22.5 ± 1.2 years; n = 213 female) and describe how these groups differ in their presentation of repetitive negative thinking, internet addiction, and subjective wellbeing. The analyses identified four latent profiles: 14.5% of students showed global dysregulation (the Low Emotion Regulation Profile), 23% were moderately dysregulated with elevated problems in goal-directed behavior (the Moderate Emotion Regulation Profile), 8% showed specific difficulties with low emotional awareness and clarity (the Low Insight Profile), and 54.4% showed adaptive emotion regulation (the High Emotion Regulation Profile). As anticipated, the Low Emotion Regulation Profile had the lowest subjective wellbeing and the highest prevalence of repetitive negative thinking and internet addiction. Students with a Low Insight Profile also showed low subjective wellbeing, but less repetitive negative thinking compared to the Low Emotion Regulation Profile. Our findings suggest that interventions aimed at improving health and wellbeing among university students should consider each student’s unique set of emotion regulation difficulties, rather than focusing on particular strategies. Further research may help determine whether emotion regulation profiles can serve as predictive indicators of varying mental health trajectories and subjective wellbeing in university students.